Empowering Students against Ethnic Bullying: Review and Recommendations of Innovative School Programs - Qiyue Wu; Fanli Jia (MDPI AG, 2023)
Despite research on anti-bullying interventions, there is no systemic approach or resources for teachers to address ethnic and race-related bullying in schools. In this article, we selectively reviewed theories and programs to help teachers identify and address ethnic bullying in their classrooms. We provide recommendations for workshops (e.g., cultural awareness training, empathy-building activities, bystander intervention, and stigma-based intervention). These anti-ethnic bullying workshops should promote understanding of different cultures, strengthen empathy for those who are different, encourage bystanders to take action, and reduce stigma and stereotypes. Through the sharing of diverse perspectives, expertise, and experiences, we hope this article can cultivate interactive dialogues and collaborations between educators and researchers to effectively address ethnic and race-related bullying.